Are the Youngsters Taking Over?: The Second Modernity and the Digital Generation - Pertierra, Raul (Archīum Ateneo, 2018)
We are currently entering a new cultural phase. While it is difficult to predict exactly its important features, a major component is the increasing youthification of culture. In an age of digital and limitless reproduction, the youth provide the most appropriate images for this cultural phase. What has brought this cultural shift about and what are its implications for society and culture? Why are the new technologies of communication so attractive to the young? Is an increase in agency for its users the main attraction? Is this agentic increase “real” and authentic or does it lead its users into a world of simulacra? This increase in human agency leads to a growing unpredictability of the future, including relationships with non-human subjects.